Influence of Digital Transformation, HR Competence, and AIS on MSME Financial Reporting Quality via Digital Literacy - Maya Maharani Khoirunnisa Hanafiah; Etty Herijawati; Shima Oktabara Kusumawardani (Komunitas Dosen Indonesia, 2026)
This study aims to examine the simultaneous effects of digital transformation, the competence of human resources (HR) in accounting, and accounting information systems on the quality of financial reporting of MSMEs in Indonesia, with digital literacy as a mediating variable. The adoption of digital technology in accounting processes has not yet been fully optimized in the MSME sector, making it necessary to analyze how the synergy between technology, human, and system factors can promote more transparent and reliable financial reporting practices. A quantitative approach was used with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis technique, involving 450 MSME respondents who met the inclusion criteria. The analysis results show that all three independent variables have a positive and significant influence both partially and simultaneously on the quality of financial reporting. Digital literacy was also proven to significantly mediate this relationship, strengthening the indirect influence of organizational input variables on financial reporting outputs. These findings underscore the importance of a holistic approach that includes HR capacity development, digital technology adoption, and the implementation of effective information systems as an integrated strategy to improve MSME financial governance. This research contributes theoretically by expanding the organization-based technology adoption model, and offers practical implications for policymakers and MSME facilitators in designing sustainable and context-specific digital transformation interventions.